2011
DOI: 10.1093/schbul/sbr029
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Developmental Trajectories of Neural Circuits in the Primate Prefrontal Cortex: Identifying Sensitive Periods for Vulnerability to Schizophrenia

Abstract: Schizophrenia is a disorder of cognitive neurodevelopment with characteristic abnormalities in working memory attributed, at least in part, to alterations in the circuitry of the dorsolateral prefrontal cortex. Various environmental exposures from conception through adolescence increase risk for the illness, possibly by altering the developmental trajectories of prefrontal cortical circuits. Macaque monkeys provide an excellent model system for studying the maturation of prefrontal cortical circuits. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 100 publications
2
93
1
Order By: Relevance
“…Male monkeys enter puberty at ∼3.5 y of age and reach full sexual maturity at 5 y, approximately equivalent to the human ages of 11 y and 16 y, respectively (25,26). By some accounts, biochemical and anatomical changes characteristic of adolescence in humans occur at an earlier, prepubertal age in the monkey prefrontal cortex (27,28), so it is not known if cognitive maturation or neurophysiological changes occur in monkeys after puberty. The contribution of prefrontal cortex to antisaccade performance has also been a matter of debate, with contrasting views favoring mechanisms of inhibiting movement toward the visual stimulus or enhancing movement away from it (29)(30)(31).…”
mentioning
confidence: 99%
“…Male monkeys enter puberty at ∼3.5 y of age and reach full sexual maturity at 5 y, approximately equivalent to the human ages of 11 y and 16 y, respectively (25,26). By some accounts, biochemical and anatomical changes characteristic of adolescence in humans occur at an earlier, prepubertal age in the monkey prefrontal cortex (27,28), so it is not known if cognitive maturation or neurophysiological changes occur in monkeys after puberty. The contribution of prefrontal cortex to antisaccade performance has also been a matter of debate, with contrasting views favoring mechanisms of inhibiting movement toward the visual stimulus or enhancing movement away from it (29)(30)(31).…”
mentioning
confidence: 99%
“…In the past two decades, numerous studies have been focused on detail changes in the functional maturation of the PFC circuitry. For example, it is now clear that the underlying synaptic refinement process in the PFC is not completed until late adolescence and early adulthood [110,111], which coincides with the period when symptoms of schizophrenia typically begin to emerge [112]. Indeed, our study indicated that the NMDA receptor subunit NR2B-to-NR2A shift does not occur during prefrontal development.…”
Section: Adolescence Is a Critical Period For Pfc Maturation  Molecumentioning
confidence: 67%
“…Importantly, D2 agonists were effective only in adult but not in prepubertal animals [115]. Many other late occurring changes in GABAergic neurons, GABAergic neurotransmission and GABA A receptors have also been demonstrated [112,116,117]. Similarly, developmental trends have been reported for the dopaminergic [118] and glutamatergic systems [119] and for interactions of these neurotransmitters with GABAergic interneurons.…”
Section: Adolescence Is a Critical Period For Pfc Maturation  Molecumentioning
confidence: 90%
See 2 more Smart Citations